Preparation method and application of magnetic organic framework-ionic liquid composite material
Through the application of magnetic organic frame-ionic liquid composite materials, the complexity and cost of detecting multiple heavy metal ions in ethanol fuel in the prior art is solved, and the effect of rapid, sensitive and simultaneous detection is achieved.
Patent Information
- Application Number
- CN202510093039.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-21
AI Technical Summary
The prior art requires sample pretreatment and expensive testing equipment when detecting multiple heavy metal ions in ethanol fuels, and it is difficult to achieve the effect of fast, sensitive and simultaneous detection of multiple ions.
The composite material formed by combining nano-Fe3O4 with zeolite imidazole frame-8 and ionic liquid is used to form a droplet in ethanol. The magnetic properties of the magnetic materials and the adsorption characteristics of the magnetic materials are used to achieve rapid adsorption and electrochemical detection.
It realizes rapid adsorption and simultaneous detection of three heavy metal ions, Cd2+, Cu2+, and Hg2+, in ethanol, simplifies the electrode surface material modification process and improves the detection sensitivity and efficiency.
Smart Images

Figure CN119901792A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to analysis and detection technology, and specifically relates to the simple synthesis of a magnetic droplet composite material with adsorption effect and its application in the simultaneous detection of multiple heavy metal ions. Background Art
[0002] The depletion of petroleum fuels and ecological problems have attracted the attention of many countries to clean and renewable alternative fuels to gasoline and diesel. Ethanol is considered to be a good alternative to automobile engine fuel due to its biodegradable and renewable characteristics. Ethanol fuel is a biofuel. Based on environmental, technical and economic aspects, it is of great significance to improve the quality of ethanol fuel. Cadmium, copper, and mercury are common heavy metal pollutants and are also pollutants present in ethanol fuel. Trace amounts of heavy metal ions in ethanol fuel accelerate the occurrence of corrosion reactions. Heavy metal ions also promote the formation of fuel deposits, catalyze oxidation reactions in hydrocarbon mixtures, and reduce the efficiency of catalytic reactors used in automobile exhaust systems. Therefore, it is of great significance to design a sensitive detection method for heavy metal ions in ethanol.
[0003] Many studies use spectroscopic techniques such as atomic absorption spectroscopy (AAS), inductively coupled plasma atomic emission spectroscopy (AES-ICP), inductively coupled plasma mass spectrometry (MS-ICP), ultraviolet visible spectrophotometry (UV-Vis) and energy dispersive X-ray fluorescence (ED-XRF). These spectroscopic techniques require sample pretreatment and expensive testing equipment. Electrochemical analysis test methods have the advantages of high sensitivity, convenient detection, and simultaneous detection of multiple ions. They are ideal for simultaneous analysis and detection of multiple heavy metal ions.
[0004] In the process of electrochemical analysis and testing, suitable electrode materials are the key factor to achieve rapid and sensitive detection. Metal organic framework (MOF) is a porous material composed of inorganic ions or groups connected with organic ligands. As an adsorbent, MOF material will have difficulty in separation in solution, which affects practical applications. Combining MOF with magnetic nanomaterials, utilizing the magnetism of magnetic materials, and using external magnetic fields for adsorption can achieve rapid collection. Ionic liquids (ILs) are salts formed by pairing asymmetric organic cations with inorganic or organic anions, and are usually liquid at room temperature. IL is used as a reaction medium for MOF synthesis, which affects the structural characteristics of MOF. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a preparation method of a magnetic organic framework-ionic liquid composite material and its application.
[0006] The specific plan is as follows:
[0007] A method for preparing a magnetic organic framework-ionic liquid composite material comprises the following steps:
[0008] Step (1): preparing a polystyrene sulfonate sodium salt (PSS) solution;
[0009] Step (2): adding nano-Fe3O4 to the PSS solution of step (1), mixing by ultrasonication, then collecting the material by magnetic attraction, and washing with deionized water to obtain a solid intermediate product;
[0010] Step (3): dissolving a certain amount of Zn(CH3COO)2 and 2-methylimidazole in 1-ethyl-3-methylimidazole tetrafluoroborate (ionic liquid, IL) to form a mixed solution;
[0011] Step (4): Disperse the solid intermediate product obtained in step (2) in the mixed solution of step (3), heat and stir in a 50° C. water bath for 3 h to obtain a brown suspension.
[0012] Step (5): The product obtained in step (4) is centrifuged and washed with ethanol for several times to obtain a composite material product.
[0013] Further, in step (1), the concentration of the polystyrene sulfonate sodium salt (PSS) solution is 0.3%;
[0014] Furthermore, in step (2), the nano-Fe3O4 is about 20 nm;
[0015] Furthermore, in step (3), Zn(CH3COO)2 is 35.8 mg, 2-methylimidazole is 134.6 mg, and 1-ethyl-3-methylimidazole tetrafluoroborate IL is 3.0 mL.
[0016] A magnetic organic framework-ionic liquid composite material, the main components of which are ferroferric oxide nanoparticles, zeolite imidazole framework-8 and ionic liquid, which are immiscible with ethanol. The material is in the form of immiscible droplets in ethanol and can quickly re-aggregate after oscillation dispersion to achieve rapid adsorption of Cd in ethanol. 2+ ,Cu 2+ , Hg 2+ The purpose of the three heavy metal ions; and this composite material can be collected by magnetic absorption. With the characteristics of rapid adsorption of the material, the material can be magnetically attracted to the surface of the magnetic glassy carbon electrode to achieve one-step electrode surface material modification, and then differential pulse voltammetry can be used to achieve Cd in ethanol 2+ , Cu 2+ , Hg 2+ Simultaneous electrochemical detection of three heavy metal ions.
[0017] An application of a magnetic organic framework-ionic liquid composite material characterized by simultaneous electrochemical detection of heavy metal ions in ethanol, the application comprising the following steps:
[0018] Step S1: Add a certain amount of magnetic organic framework-ionic liquid composite material to Cd 2+ , Cu 2+ , Hg 2+ ethanol, and adsorb heavy metal ions by shaking (10s);
[0019] Step S2: Using the built-in magnet in the magnetic glassy carbon electrode to attract the magnetic organic framework-ionic liquid composite material after the heavy metal ions are adsorbed in step S1 and modified on the magnetic glassy carbon electrode.
[0020] Furthermore, in step S1, Cd 2+ , Cu 2+ , Hg 2+ The concentration is 1~100μmol / L.
[0021] Furthermore, the modified magnetic glassy carbon electrode was used as the working electrode, the platinum rod electrode was used as the counter electrode, the saturated calomel electrode was used as the reference electrode, and the electrolyte was an acetic acid-sodium acetate buffer solution. Differential pulse voltammetry was used to detect the contents of three heavy metal ions in ethanol.
[0022] Furthermore, the concentration of the acetic acid-sodium acetate buffer solution is 0.1 mol / L and the pH is 4.
[0023] The beneficial effects of the present invention are as follows: the composite material synthesized by the present invention has adsorption characteristics, presents an immiscible droplet shape in an ethanol solution, can be quickly re-aggregated after being shaken and dispersed, and realizes rapid adsorption of Cd in an organic solvent ethanol. 2+ , Cu 2 + , Hg 2+ The purpose of three heavy metal ion detection. This material simplifies the layer-by-layer modification on the electrode surface, and can achieve one-step electrode surface material modification. The differential pulse voltammetry method is used to realize the detection of Cd 2+ , Cu 2+ , Hg 2+ Simultaneous electrochemical detection of three heavy metal ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a scanning electron microscope image of the composite material Fe3O4 / ZIF-8 / IL of the present invention, the left image is 100 μm, and the right image is 5 μm.
[0025] Figure 2 It is the X-ray diffraction pattern of the composite material Fe3O4 / ZIF-8 / IL of the present invention.
[0026] Figure 3 Fig. 1 is a feasibility test diagram for the application of simultaneous electrochemical detection of heavy metal ions in ethanol developed for the characteristics of the composite material Fe3O4 / ZIF-8 / IL of the present invention.
[0027] Figure 4 A condition optimization diagram for the simultaneous electrochemical detection of heavy metal ions in ethanol developed for the characteristics of the composite material Fe3O4 / ZIF-8 / IL of the present invention, wherein a and b represent the effects of the pH of the buffer solution and the amount of ethanol on the electrochemical signal, respectively.
[0028] Figure 5 The detection diagram of the application of the composite material Fe3O4 / ZIF-8 / IL of the present invention for the simultaneous electrochemical detection of heavy metal ions in ethanol, when the concentration of 0.1 mol / L acetic acid-sodium acetate buffer solution and pH is 4, the application of the present invention has an effect on the detection of different concentrations of Cd 2+ , Cu 2+ , Hg 2+ The response curve of differential pulse voltammetry and the standard curve, where a, c, and e are respectively Fe3O4 / ZIF-8 / IL composites for detecting 1-100 μmol / LCd 2+ , Cu 2+ , Hg 2+ DPV response of ethanol solution of b, d, and f are the simultaneous determination of different concentrations of Cd 2+ , Cu 2+ , Hg 2+ Standard curve diagram of . DETAILED DESCRIPTION
[0029] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0030] The present invention provides a method for preparing a magnetic organic framework-ionic liquid composite material, which is characterized by comprising the following steps:
[0031] Step (1): preparing a polystyrene sulfonate sodium salt PSS solution (concentration: 0.3%);
[0032] Step (2): adding nano-Fe3O4 (20 nm) to the PSS solution of step (1) and mixing by ultrasonication; then collecting the material by magnetic attraction and washing with deionized water to obtain a solid intermediate product;
[0033] Step (3): dissolve 35.8 mg of Zn(CH3COO)2 and 134.6 mg of 2-methylimidazole in 3.0 mL of 1-ethyl-3-methylimidazole tetrafluoroborate to form a mixed solution;
[0034] Step (4): dispersing the solid intermediate product obtained in step (2) in the mixed solution of step (3), heating in a 50° C. water bath with stirring for 3 h to obtain a brown suspension;
[0035] Step (5): The product obtained in step (4) is centrifuged and washed with ethanol for several times to obtain a composite material product.
[0036] like Figure 1 Scanning electron microscopy image of the composite material Fe3O4 / ZIF-8 / IL is shown.
[0037] The composite material has good dispersibility, the material size is relatively uniform, and the material has a relatively regular morphology. ZIF-8 synthesized in IL environment maintains a crystalline structure.
[0038] like Figure 2 X-ray diffraction pattern of the composite material Fe3O4 / ZIF-8 / IL composite material is shown.
[0039] The characteristic diffraction peaks of the synthesized material Fe3O4 / ZIF-8 / IL at 2θ=30.09°, 35.42°, 43.05°, 53.39°, 56.94°, 62.51° and 73.95° correspond to the (220), (311), (400), (422), (511), (440) and (533) crystal planes, indicating that the structure of Fe3O4 was maintained during the synthesis of Fe3O4 / ZIF-8 / IL. In addition, the characteristic diffraction peaks at 2θ=7.28°, 10.16°, 12.62°, 14.7°, 16.28° and 18.04° correspond to the (011), (002), (112), (022), (013) and (222) crystal planes of ZIF-8, respectively. The crystal structure of ZIF-8 synthesized under IL environment is preserved. Due to the influence of IL, the peak intensity of ZIF-8 in the composite material is different from that of standard ZIF-8. In general, the synthesized Fe3O4 / ZIF-8 / IL retains the magnetic separation ability of Fe3O4 and has the efficient adsorption performance of ZIF-8. The addition of IL makes the composite material present an immiscible droplet shape in ethanol.
[0040] like Figure 3 Figure 4 shows the feasibility test of the developed composite material Fe3O4 / ZIF-8 / IL for application in simultaneous electrochemical detection of heavy metal ions in ethanol.
[0041] Heavy metal ions are prone to redox reactions. When heavy metal ions undergo redox reactions with heavy metal elements, corresponding peaks will appear in electrochemical tests. The peak potentials are different according to the types of heavy metal ions, and the heavy metal ions can be distinguished. As shown in the figure, there are three electrochemical dissolution peaks at -0.8V, -0.1V, and 0.2V. According to the redox potentials of the three ions, it can be determined that the electrochemical dissolution peak at -0.8V is Cd 2+ , the electrochemical dissolution peak at -0.1 V is Cu 2+ , the electrochemical stripping peak at 0.2V is Hg 2+ The constructed electrochemical sensor can simultaneously detect three heavy metal ions Cd 2+ , Cu 2+ , Hg 2+ .
[0042] like Figure 4 The optimization diagram of the effect of buffer solution pH and ethanol solution dosage on electrochemical signals when the electrochemical sensor constructed with the material Fe3O4 / ZIF-8 / IL detects various heavy metal ions.
[0043] In order to obtain the optimal sensing performance of the electrochemical sensor constructed by the material Fe3O4 / ZIF-8 / IL, the factors affecting the sensor signal were determined and optimized during the experiment, among which the influencing factors were the electrolyte pH (3-7) and the amount of ethanol solution (1-5mL). Differential pulse voltammetry was used to record the dissolution peaks of heavy metal ions under different conditions, and each group of experiments was repeated three times under the same conditions. As shown in Figure a, when the pH value of the NaAc-HAc buffer solution was 4, the dissolution peaks of the three heavy metal ions measured the largest electrochemical signal. In the case of too strong or too weak acidity, the performance of the material may be affected, resulting in unstable electrochemical signals and failure to achieve the optimal detection effect. When the amount of ethanol solution dripped into the material is constant, the more heavy metal ions contained in the solution, the stronger the electrochemical signal obtained. When the ethanol solution of heavy metal ions is 2mL, the optimal electrochemical signal is measured. When the solution exceeds 2mL, the material may not be able to effectively adsorb heavy metal ions in a short time due to the large volume of the solution, resulting in a decrease in the electrochemical signal.
[0044] like Figure 5 The detection diagram shown is an application of the simultaneous electrochemical detection of heavy metal ions in ethanol developed by the composite material Fe3O4 / ZIF-8 / IL of the present invention.
[0045] Take 2 μL of Fe3O4 / ZIF-8 / IL liquid material and 2 mL of different concentrations of Cd 2+ , Cu 2+ , Hg 2+The magnetic material was dropped into the solution containing heavy metal ions with ethanol solution (1, 10, 30, 50, 80, 100 μmol / L) and slightly shaken to disperse the material in the solution. After the material quickly aggregated, it was modified on the surface of the magnetic glassy carbon electrode. Finally, the electrochemical signals generated by the three ions were tested using differential pulse voltammetry (DPV). Each group of experiments was conducted three times under the same conditions. As shown in the figure, it can be clearly seen that Cd 2+ The electrochemical stripping peak of Cu 2+ The electrochemical stripping peak of Hg 2+ The electrochemical dissolution peak of Cd is at 0.2V. The electrochemical signal peaks of the three ions increase with the increase of ion concentration. Based on the known concentrations of the three heavy metal ions and the peak values of the dissolution peaks produced at the concentrations measured experimentally, we established a concentration-peak standard curve. 2+ , Cu 2+ , Hg 2+ The peak values of the three ions and their concentrations showed a good linear relationship between 1 and 100 μmol / L. 2+ The linear regression equation is y = 0.1730x-0.12125 (R 2 =0.999), Cu 2+ The linear regression equation is y = 0.07223x-0.039675 (R 2 =0.997), Hg 2+ The linear regression equation is y = 0.5243x-0.4828 (R 2 =0.998), (where x is Cd 2+ , Cu 2+ , Hg 2+ The electrochemical sensor is sensitive to Cd 2+ , Cu 2+ , Hg 2+ The detection limits are 254.39nM, 415.34nM and 9.458nM respectively. The prepared heavy metal ion solution of unknown concentration can be measured for electrochemical peak value according to the above method, and the obtained peak value can be put into the linear regression equation to obtain the concentration of heavy metal ions in the unknown solution, thereby realizing the detection of heavy metal ion concentration.
Claims
1. A method for preparing a magnetic organic framework-ionic liquid composite material, characterized in that: The following steps are involved: Step (1): preparing a polystyrene sulfonate sodium salt PSS solution; Step (2): adding nano-Fe3O4 to the PSS solution of step (1) and mixing by ultrasonication; then collecting the material by magnetic attraction and washing with deionized water to obtain a solid intermediate product; Step (3): dissolving a certain amount of Zn(CH3COO)2 and 2-methylimidazole in 1-ethyl-3-methylimidazole tetrafluoroborate to form a mixed solution; Step (4): dispersing the solid intermediate product obtained in step (2) in the mixed solution of step (3), heating in a 50° C. water bath with stirring for 3 h to obtain a brown suspension; Step (5): The product obtained in step (4) is centrifuged and washed with ethanol for several times to obtain a composite material product.
2. The method for preparing the magnetic organic framework-ionic liquid composite material according to claim 1, characterized in that: The concentration of the PSS solution in step (1) is 0.3%; In the step (2), the nano Fe3O4 is 20 nm; In the step (3), the amount of Zn(CH3COO)2, the amount of 2-methylimidazole, the amount of 134.6 mg, and the amount of 1-ethyl-3-methylimidazole tetrafluoroborate IL were 3.0 mL.
3. A magnetic organic framework-ionic liquid composite material, characterized in that: Prepared by the method according to any one of claims 1 to 2.
4. Application of a method for preparing a magnetic organic framework-ionic liquid composite material, characterized in that: Application of the magnetic organic framework-ionic liquid composite material prepared by the method described in any one of claims 1 to 2 for simultaneous electrochemical detection of multiple heavy metal ions in ethanol.
5. The use of the method for preparing a magnetic organic framework-ionic liquid composite material according to claim 4, characterized in that: The following steps are involved: Step S1: Add a certain amount of magnetic organic framework-ionic liquid composite material to Cd 2+ , Cu 2+ , Hg 2+ of ethanol, shake for 10 seconds; Step S2: Using the magnet built into the magnetic glassy carbon electrode, the magnetic organic framework-ionic liquid composite material after adsorbing heavy metal ions in step S1 is attracted to the surface of the magnetic glassy carbon electrode to achieve electrode surface material modification.
6. The use of the method for preparing a magnetic organic framework-ionic liquid composite material according to claim 5, characterized in that: The modified magnetic glassy carbon electrode was used as the working electrode, the platinum rod electrode was used as the counter electrode and the saturated calomel electrode was used as the reference electrode. Differential pulse voltammetry was used to detect the contents of three heavy metal ions in ethanol.
Citation Information
Patent Citations
Preparation and application of magnetic nano-composite material gamma-Fe2O3 / PDA (Polydopamine)-GA (Gallic Acid)
CN103721688A
Novel magnetic Fe / C@ MOF composite absorbent and preparation method thereof
CN104096542A
Magnetic hyperbranched polymer or magnetic hyperbranched polymer derivative blood heavy metal ion adsorbent and preparation method and application thereof
CN106902777A
Zeolite imidazate framework-functionalized ionic liquid composite material and preparation method and application thereof
CN106964316A
Ionic liquid magnetic zeolite imidazate nano material as well as preparation method and application thereof
CN109107535A